2008
DOI: 10.1063/1.2918912
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbit analysis demonstrates genetic constraints, variability, and switching in Drosophila courtship behavior

Abstract: Ruedi Stoop and Benjamin I. Arthur, Jr. Institute for Neuroinformatics ETHZ/UNIZH, Winterthurerstr. We use symbolic dynamics to describe Drosophila courtship communication. We posit that behavior should be defined in terms of irreducible periodic orbits of fundamental acts. This leads to a first operational definition of behavior, which allows for a fine grained quantitative analysis of behavior. We obtain evidence that during Drosophila courtship, individual characteristics of the protagonists are exchanged (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 28 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…We found that despite an extremely large variability of individual behaviors, to the vast majority of the individuals, the classes are distinguishable. 6 This supports the hypothesis that PC conveys mating suitability, including individual profiles. On the class level, the areas of greatest dissimilar behavior (dark bands and dark subdiagonal parts) indicate a maximally spread communication code between normal males and females, which we believe cannot be accidental.…”
Section: Detailed Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…We found that despite an extremely large variability of individual behaviors, to the vast majority of the individuals, the classes are distinguishable. 6 This supports the hypothesis that PC conveys mating suitability, including individual profiles. On the class level, the areas of greatest dissimilar behavior (dark bands and dark subdiagonal parts) indicate a maximally spread communication code between normal males and females, which we believe cannot be accidental.…”
Section: Detailed Resultssupporting
confidence: 75%
“…After characterizing each file by means of its behavioral vectorb, we calculated the scalar product between the different vectors, and, in order to compare class behavior, we also considered class behavior by averaging over the protagonists of each class (this pooling can be justified 6 ). We found that despite an extremely large variability of individual behaviors, to the vast majority of the individuals, the classes are distinguishable.…”
Section: Detailed Resultsmentioning
confidence: 99%
See 3 more Smart Citations